LITERATURE REVIEW: SENSITIVITY AND SPECIFICITY OF VDRL AND RPR AS SCREENING TESTS OF SYPHILIS IN PREGNANT WOMEN - Kadarusman, Tamara Audrey; Thirafi, Sacharissa Zerlina Tsarwah; Bangsa, Niki Kusuma; Widyatama, Rufina Adelia; Nugroho, Lutfi Dewanda; Surya, Prima Ardiansah; Lestari, Pudji (Universitas Airlangga, 2021)
Early detection of syphilis, especially during pregnancy, is important to prevent comorbidities for the mother and the baby. This study aims to determine whether VDRL is more sensitive and specific than RPR as a diagnostic screening test for syphilis infection in pregnant women. Literature searches for relevant articles were conducted in PubMed, Cochrane, and Proquest using the keywords